Djibouti: small state strategy at a crossroads. Issue 1 (2nd January 2016) - Styan, David
Abstract: Geography and politics indicate Djibouti would be a particularly weak and ineffectual 'small state'. Located on a bridgehead between the poorest parts of Africa and Arabia, it is continental Africa's smallest state by population and is devoid of natural resources. The text demonstrates that Djibouti has been able to transform weakness and liabilities stemming from its geo-strategic location, sandwiched between large neighbours and key maritime shipping lanes, into a lucrative 'resource'. This has been achieved via creative diplomacy, fostering ties with a diverse range of states, translating acute dependence into economic and diplomatic capital. The text focuses primarily upon diplomatic strategies, while addressing broader concerns of small states' energy, infrastructure and development policies.